Assessing the Roles of Molecular Markers of Antimalarial Drug Resistance and the Host Pharmacogenetics in Drug-Resistant Malaria - Peter Hodoameda; Nancy Odurowah Duah-Quashie; Neils Ben Quashie (Journal of Tropical Medicine)
Malaria caused by the Plasmodium parasites is a major public health concern in malaria-endemic regions with P. falciparum causing the most severe form of the disease. The use of antimalarial drugs for the management of the disease proves to be one of the best methods to manage the disease. Unfortunately, P. falciparum has developed resistance to almost all the current in-use antimalarial drugs. Parasite development of resistance is primarily caused by both parasite and host genetic factors. The parasite genetic factors involve undergoing mutation in the drug target sites or increasing the drug target gene copy number to prevent the intended action of the antimalarial drugs. The host pharmacogenetic factors which determine how a particular antimalarial drug is metabolized could result in variations of drug plasma concentration and consequently contribute to variable treatment outcomes and the emergence or propagation of resistant parasites. Since both host and parasite genomes play a role in antimalarial drug action, a key question often asked is, “which of the two strongly drives or controls antimalarial drug resistance?” A major finding in our recent study published in the Malaria Journal indicates that the parasite’s genetic factors rather than the host are likely to energize resistance to an antimalarial drug. However, others have reported contrary findings suggesting that the host genetic factors are the force behind resistance to antimalarial drugs. To bring clarity to these observations, there is the need for deciphering the major driving force behind antimalarial drug resistance through optimized strategies aimed at alleviating the phenomenon. In this direction, literature was systematically reviewed to establish the role and importance of each of the two factors aforementioned in the etiology of drug-resistant malaria. Using Internet search engines such as Pubmed and Google, we looked for terms likely to give the desired information which we herein present. We then went ahead to leverage the obtained information to discuss the globally avid aim of combating antimalarial drug resistance.